Assessment of in vitro Sun Protection Factor (SPF) and rheological profile of commercial infant sunscreens - Fernanda Daud Sarruf; Daniela D'Almeida Peres; Deborah de Oliveira Nishikawa; Vladi Olga Consiglieri; Telma Mary Kaneko; Maria Valéria Robles Velasco; André Rolim Baby (São Paulo State University (UNESP), 2013)
This research focused on the measurement of spectral transmittance using an integrating sphere to estimate the Sun Protection Factor (SPF) of commercial sunscreens oriented for child use. Commercially available SPF 30 sunscreens (A, B and C) were selected and assessed by the following methodology: pH measurement; rheological profile analysis; and in vitro SPF estimation by spectroscopy. Samples A, B and C exhibited, respectively, pH values of 7.8, 7.4 and 7.0. The rheological profile identified the systems as pseudoplastic nonNewtonian semisolids with hysteresis loops. The t-test (p < 0.05) was used to confront the claimed SPF (SPF = 30) with that estimated by spectroscopy. In vitro tests are considered of utmost importance in the cosmetic field, since their results may be used to validate submission to subsequent in vivo efficacy experiments. According to our results, sunscreens A, B and C generated SPF values without any significant difference from those claimed on the commercial sunscreen labels. The measurement of spectral transmittance with an integrating sphere proved to be a convenient, fast and reproducible method for SPF estimation.